Genetic variability of Plasmodium malariae dihydropteroate synthase (dhps) in four Asian countries. - Naowarat Tanomsing; Mayfong Mayxay; Paul N Newton; Francois Nosten; Christiane Dolecek; Tran Tinh Hien; Nicholas J White; Nicholas P J Day; Arjen M Dondorp; Mallika Imwong (PLoS ONE)
The dihydropteroate synthase (dhps) genes of 44 P. malariae strains from four Asian countries were isolated. Only a limited number of polymorphisms were observed. Comparison with homologous mutations in other Plasmodium species showed that these polymorphisms are unlikely to be associated with sulfadoxine resistance.